Implementation of the Standards‐Based Management and Recognition approach to quality improvement in maternal, newborn, and child health programs in low‐resource countries. (23rd June 2015) - Necochea, Edgar; Tripathi, Vandana; Kim, Young‐Mi; Akram, Nabeel; Hyjazi, Yolande; da Luz Vaz, Maria; Otolorin, Emmanuel; Pleah, Tsigue; Rashidi, Tambudzai; Bishanga, Dustan
Abstract: The Standards‐Based Management and Recognition (SBM‐R; Jhpiego, Baltimore, MD, USA) approach to quality improvement was developed by Jhpiego to respond to common challenges faced by health systems in low‐resource settings, including poor pre‐service education, lack of resources for conventional supervisory models, and weak health information systems. Since its introduction in Brazil in 1997, SBM‐R has been implemented in approximately 30 countries and continues expanding to new places and service delivery areas. The present article: (1) describes key steps in the SBM‐R methodology focusing on provider performance assessment using evidence‐based standards; and (2) presents examples of improvements in provider performance in maternal, newborn, and child health care following SBM‐R implementation derived from routine program data, quasi‐experimental evaluations, and in‐depth case studies. SBM‐R incorporates evidence‐based methods that are known to have positive effects on healthcare quality, including audit and feedback, educational outreach visits, and checklist usage; however, further rigorous research is needed to document the population‐level impacts of the SBM‐R approach.